Tribological behaviour of high-carbon carbide-free nanostructured bainitic steel - Gupta S.K.; Manna R.; Chattopadhyay K. (My University, 2025)
This research focuses on the development of carbide-free nanostructured bainitic steel through the process of austempering at 250°C. The selected steels are also patented at 550°C, to get fine pearlitic structure. In austempered steels, microscopic analyses encompassing optical, scanning, transmission electron microscopy and X-ray diffraction revealed the presence of nanoscale bainite, filmy and blocky austenite. In contrast, lamellar pearlite was observed in the patented steels. With increase in the austempering duration, the extent of bainite improved, while the volume percentage of blocky retained austenite (RA) decreased. The tribological performance of high-carbon bainitic steels is compared with patented one of same composition against a tungsten-carbide counter disc. The specific wear rate as well as coefficient of friction decreases with rise in load from 10 to 50 N. The hardening volume of B15VA-1 sample is greater than that of B15VA-2 and P15VA, and it is mainly due to the transformation of blocky RA to strain-induced martensite. The bainitic pins with higher hardness exhibited superior tribological response than the pearlitic ones. SEM analysis of worn surfaces confirmed that at lower load (10 N), abrasive wear occurs, but at higher load (50 N), wear mechanism changes to adhesive along with abrasive in bainitic steel and oxidative wear along with adhesive and abrasive wear in pearlitic steel. © Indian Academy of Sciences 2024.